Attendance or Response Ware System using Raspberry Pi - Leow, Hui Si (Nanyang Technological University, 2019)
Response Ware System (RWS) is created for Lectures, Student and Guests for them to communicate better and to encourage student or guest to speak up and ask question by allowing them to post question anomalously. In additional, since RWS is a web application, it is portable and can be easily access by any devices